Salzburger Kunstverein Jahresbericht 1993. - Eiblmayr, Silvia; Harb, Karl; Schneider, Herbert; Salzburger Kunstverein, Salzburg (Salzburg : Salzburger Kunstverein, 1994)
Sieverding, Katharina ; Zobernig, Heimo ; Oehlen, Albert ; Konrad, Aglaia ; Locher, Thomas ; Weigand, Hans ; Kabakov, Ilya ; Rosenberg, Aura ; Krystufek, Elke ; Lankton, Greer ; Helm, Gerlinde ; Magnus, Rosita ; Bolt, Ronald ; Maderna, Marianne ; Lienbacher, Ulrike
Duits
boek